Nilai-nilai Pendidikan Islam dalam Qashidah Jaljalut: Telaah atas Kitab Manba’ Ushul Hikmah dan Syams Al-Ma’arif - Jamal Abdul Nasir; Agus Abdussalam (SETYAKI : Jurnal Studi Keagamaan Islam, 2025)
The purpose of this research is to identify and analyze the Islamic educational values contained in the Qashidah Jaljalut, a classical text often associated with mystical and esoteric practices. This study arises from a conceptual gap in the understanding of Islamic education sources. While Islamic education is generally linked to formal tarbiyah literature, there exists a prevailing perception that the Qashidah Jaljalut, as found in Manba’ Ushul Hikmah and Shams al-Ma’arif, is merely a product of occultism and supernatural tradition. This research seeks to critically verify such claims and to uncover the educational and spiritual dimensions embedded within the text as an antithesis to those assumptions. Using a qualitative library research design, this study employs a descriptive-analytical approach and content analysis techniques to interpret the text within the framework of fundamental Islamic values. The analysis draws upon core principles of iman (faith), tawhid (monotheism), ibadah (worship), akhlaq (morality), and muamalah (social relations) as benchmarks of Islamic education. The findings reveal that despite its mystical presentation, the Qashidah Jaljalut conveys profound messages of Islamic pedagogy and spirituality. It emphasizes the strengthening of faith, recognition of divine oneness, disciplined worship, moral refinement, and ethical social behavior. These elements demonstrate that the Qashidah Jaljalut functions not only as a literary or mystical work but also as a medium for moral and spiritual formation in the tradition of Islamic education. Therefore, this study contributes to recontextualizing classical Islamic texts within contemporary educational discourse, highlighting their potential relevance in nurturing holistic religious understanding.